A Generalized Framework for the Assessment of Household Financial Vulnerability - Leika, Mindaugas (IMF Working Papers; Working Paper, 2017)
Household financial fragility has received considerable attention following the global financial crisis, but substantial gaps remain in the analytical underpinnings of household financial vulnerability assessment, as well as in data availability. This paper aims at integrating the contributions in the literature in a coherent fashion. The study proposes also analytical and estimation extensions aimed at improving the quality of estimates and allowing the assessment of household financial vulnerability in presence of data limitations. The result of this effort is a comprehensive framework, that has wide applicability to both advanced and developing economies. For illustrative purposes the paper includes a detailed application to one developing country (Namibia).